2017
DOI: 10.1248/bpb.b16-00802
|View full text |Cite
|
Sign up to set email alerts
|

Effects of <i>Astragalus</i> Combined with <i>Angelica</i> on Bone Marrow Hematopoiesis Suppression Induced by Cyclophosphamide in Mice

Abstract: Danggui Buxue Tang (DBT), a combination of Astragalus and Angelica at a 5 : 1 ratio, mainly promotes hematopoiesis. However, in the clinic, the combination ratio of Astragalus and Angelica to treat low hematopoietic function is not an absolute 5 : 1 ratio, suggesting that the herbs may promote hematopoiesis better after being combined at a certain range of ratios. The objective of this study is to investigate the effect of different ratio combinations of Astragalus and Angelica on bone marrow hematopoiesis sup… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
18
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 22 publications
(19 citation statements)
references
References 22 publications
1
18
0
Order By: Relevance
“…A study of an aging model of HSCs induced by tert-butyl hydroperoxide (t-BHP) discovered that AR, ASR, and their compatibility could inhibit the aging of HSCs and promote HSC proliferation and cell cycle transformation. In particular, the compatibility of AR and ASR (1:1) had the strongest effect (Zhang et al, 2017) and could promote active components [FRA, FRM, AST, CAL, and CLG (calycosin-7-glucoside)] dissolution and absorption in isolated small intestine in rats (Li et al, 2017). It is suggested that the active components (FRA, FRM, AST, CAL, and CLG) may be the main effective substances of the compatibility of AR and ASR that promote hematopoiesis.…”
Section: Introductionmentioning
confidence: 99%
“…A study of an aging model of HSCs induced by tert-butyl hydroperoxide (t-BHP) discovered that AR, ASR, and their compatibility could inhibit the aging of HSCs and promote HSC proliferation and cell cycle transformation. In particular, the compatibility of AR and ASR (1:1) had the strongest effect (Zhang et al, 2017) and could promote active components [FRA, FRM, AST, CAL, and CLG (calycosin-7-glucoside)] dissolution and absorption in isolated small intestine in rats (Li et al, 2017). It is suggested that the active components (FRA, FRM, AST, CAL, and CLG) may be the main effective substances of the compatibility of AR and ASR that promote hematopoiesis.…”
Section: Introductionmentioning
confidence: 99%
“…Studies show that Danggui Buxue Tang has inhibitory effects on bone marrow hematopoiesis suppression induced by Cyclophosphamide in mice by spurring the synthesis and secretion of hematopoietic growth factor and the proliferation of hematopoietic progenitor cells in mice. [ 42 ] It may have benefits on the patient's anemia.…”
Section: Discussionmentioning
confidence: 99%
“…Calycosin glycoside, calycosin, formononetin, and astragaloside IV are the characteristic components of Astragalus, and ferulic acid is the characteristic component of Angelica [ 7 ]. Therefore, the components were measured to identify Astragalus and Angelica by ultra performance liquid chromatography tandem mass spectrometry (UPLC-MS/MS) by our research team previously on a Waters-Xevo-G2-S QTof UPLC-MS/MS instrument (Acquity system, V4.1 Masslynx chromatography workstation, Waters Co., USA) [ 8 ]. The contents of effective components in Astragalus extract were as follows: Astragalus calycosin glycoside 462.96 μ g/g crude herb, calycosin 351.62 μ g/g crude herb, formononetin 52 μ g/g crude herb, and astragaloside 33.38 μ g/g crude herb.…”
Section: Methodsmentioning
confidence: 99%
“…The contents of the active constituents in the extract of Angelica were as follows: ferulic acid 328.74 μ g/g crude herb. The contents of effective components in the extract of Astragalus–Angelica 1:1 compatibility are ferulic acid 438.86 μ g/g crude herb, Astragalus calycosin glycoside 438.86 μ g/g crude herb, calycosin 267.82 μ g/g crude herb, formononetin 44.34 μ g/g crude herb, and astragaloside 12.46 μ g/g crude herb [ 8 ]. Studies have shown that the five chemical components can be absorbed into the plasma [ 9 ] through small intestine [ 10 ] and are related to vascular remodeling factors.…”
Section: Methodsmentioning
confidence: 99%